Systematic metabolic engineering enables highly efficient production of vitamin A in Saccharomyces cerevisiae - Yi Shi; Shuhuan Lu; Xiao Zhou; Xinhui Wang; Chenglong Zhang; Nan Wu; Tianyu Dong; Shilong Xing; Ying Wang; Wenhai Xiao; Mingdong Yao (Synthetic and Systems Biotechnology)
Vitamin A is a micronutrient critical for versatile biological functions and has been widely used in the food, cosmetics, pharmaceutical, and nutraceutical industries. Synthetic biology and metabolic engineering enable microbes, especially the model organism Saccharomyces cerevisiae (generally recognised as safe) to possess great potential for the production of vitamin A. Herein, we first generated a vitamin A-producing strain by mining β-carotene 15,15′-mono(di)oxygenase from different sources and identified two isoenzymes Mbblh and Ssbco with comparable catalytic properties but different catalytic mechanisms. Combinational expression of isoenzymes increased the flux from β-carotene to vitamin A metabolism. To modulate the vitamin A components, retinol dehydrogenase 12 from Homo sapiens was introduced to achieve more than 90 % retinol purity using shake flask fermentation. Overexpressing POS5Δ17 enhanced the reduced nicotinamide adenine dinucleotide phosphate pool, and the titer of vitamin A was elevated by almost 46 %. Multi-copy integration of the key rate-limiting step gene Mbblh further improved the synthesis of vitamin A. Consequently, the titer of vitamin A in the strain harbouring the Ura3 marker was increased to 588 mg/L at the shake-flask level. Eventually, the highest reported titer of 5.21 g/L vitamin A in S. cerevisiae was achieved in a 1-L bioreactor. This study unlocked the potential of S. cerevisiae for synthesising vitamin A in a sustainable and economical way, laying the foundation for the commercial-scale production of bio-based vitamin A.